What to expect from iOS 5. - Bookwalter, J. R.
Just when you thought you knew iOS 4.3, rumors of a summer release for iOS 5 start building steam. Here's how we predict Apple's next mobile OS will change your iPhone, iPad, and iPod touch.
Keywords: iOS (Electronic resource); iOS 5.; Voice commands; Wi-Fi Sync